Adolescents' Resilience During COVID-19 Pandemic and Its Mediating Role in the Association Between SEL Skills and Mental Health - Grazzani, Ilaria; Agliati, Alessia; Cavioni, Valeria; Conte, Elisabetta; Gandellini, Sabina; Lupica Spagnolo, Mara; Ornaghi, Veronica; Rossi, Francesca Micol; Cefai, Carmel; Bartolo, Paul; Camilleri, Liberato; Oriordan, Mollie Rose (Frontiers in Psychology, 2022)
The main purpose of this paper is to investigate the role of social and emotional skills and resilience in explaining mental health in male and female adolescents, during the COVID-19 pandemic. Three self-report questionnaires were administered to 778 participants aged between 11-16 years (mean age = 12.73 years; SD = 1.73) and recruited from 18 schools in Northern Italy. The SSIS-SELb-S and the CD-RISC 10 assessed social and emotional learning (SEL) and resilience skills respectively, while the Strengths and Difficulties Questionnaire (SDQ) was used to measure mental health in terms of internalizing problems, externalizing problems, and prosocial behavior. We found that SEL and resilience skills were positively and significantly associated with each other, negatively associated with internalizing and externalizing problems, and positively related to prosocial behavior. Three linear regression analyses showed the significant role of resilience, age, and gender in explaining the variance of internalizing problems; the significant role of SEL skills, resilience, age, and gender in explaining the variance of externalizing problems; and the role of SEL skills, age, and gender in explaining prosocial behavior. Importantly, we found that resilience fully mediated the relationship between SEL and internalizing problems, partially mediated the relationship between SEL and externalizing problems, and didn’t mediate the relationship between SEL and prosocial behavior. The paper concludes with a discussion of the limitations of the study as well as its practical implications.